A new anesthetic protocol to medullary nerve roots access in rats - Santos,Deivid Ramos dos (2021)
ABSTRACT Purpose: To describe a new anesthetic protocol medullary and nerve roots access and in Rattus norvegicus. Methods: Seventy female Wistar rats (n=70) were used. The animals were randomly divided into two laminectomy groups: cervical (n=40) and thoracic (n=30). In cervical group, a right posterior hemilaminectomy was performed to access the nerve roots. In thoracic group, a laminectomy of the eighth thoracic vertebra was accomplished. Thirty-five rats (20 cervical and 15 thoracic) were submitted to old anesthetic protocol (ketamine 70 mg/kg plus xylazine 10 mg/kg); and the 35 other animals (20 cervical and 15 thoracic) were submitted to a new anesthetic protocol (ketamine 60 mg/kg,xylazine 8 mg/kg and fentanyl 0.03 mg/kg). Results: The time to complete induction was 4.15 ±1.20 minin ketamine, xylazine and fentanyl group, and it was 4.09 ±1.47 min in the ketamine and xylazine group. There was no correlation in the time required to perform the cervical laminectomy in the old anesthetic protocol. In all groups, the animals submitted to the old anesthetic protocol had a higher level of pain on the first and third postoperative days than the animals submitted to the new anesthetic protocol. Conclusions: The new anesthetic protocol reduces the surgical time, allows better maintenance of the anesthetic plan, and brings more satisfactory postoperative recovery.